The Analysis of Ecotourism Principle on Methods of Waste Disposal to Minimize Negative Impacts in Baluran National Park - Anisa Sekarningrum (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
Ecotourism has been identified as a potential source of tourism development, particularly in conservation areas such as national parks. Ecotourism principles should be implemented in order to achieve the goals of sustainable tourism. One of the ecotourism principles for minimizing the negative impacts of tourism activities is waste disposal methods. Baluran National Park is a conservation site with the primary goal of preserving its ecosystem while also being accessible to tourists. As one of the potential ecotourism sites, the purpose of this study was to use qualitative research to investigate the practices of implementing ecotourism principles on waste disposal methods in order to reduce the negative impact caused by tourism activity in Baluran National Park. The observation will concentrate on how the six waste disposal methods (Ceballos-Lascurain, 1996) are implemented in the main tourist areas of Baluran National Park, which are Batangan, Bekol, and Bama. The results show that four waste disposal methods, namely reducing waste with non-toxic materials, reusing materials on-site or off-site recycling, efficient recycling by sorting materials, and material control, have not been implemented in Baluran National Park. Meanwhile, composting or anaerobically digesting biodegradable wastes and purchasing materials from local people are two methods that have been applied, but not thoroughly.